A COMPARATIVE STUDY OF AWARENESS AMONG THIRD YEAR FEMALE UNDERGRADUATES FROM THE MEDICAL TECHNOLOGY AND PHARMACY DEGREE PROGRAMS IN THE UNIVERSITY OF SANTO TOMAS ON COMORBIDITIES OF POLYCYSTIC OVARIAN SYNDROME (PCOS) - Camaya, Carla Gabrielle; Fadreguilan, K; Loreto, K; Nisay, N; Perez, AV; Quinez, CJ; Rafael, JR; Garcia-Meim, R (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Polycystic Ovarian Syndrome (PCOS) is a female reproductive disorder characterized by hormonal imbalances, which can result in a variety of comorbidities. In the Philippine setting, there is an evident lack of literature regarding PCOS, which necessitates a study that explores the present status of the aforementioned aspect. Due to this, the aim of the study is to establish a statistical significance on the comparison between the awareness on PCOS comorbidities of two health allied student groups: female students of the Medical Technology and Pharmacy programs and to contribute to lack of local PCOS studies. METHODOLOGY The research employed an online dissemination of the designed 5-point Likert scale questionnaire to gauge the awareness of the intended respondents. The statistical analysis utilized an F-test followed by a two sample T-test assuming equal variances. RESULTS The main findings of the study are as follows: both student groups were generally aware of PCOS comorbidities, however, a low level of awareness on cardiovascular diseases and Insulin Resistance was observed. In contrast the population had a high level of awareness regarding reproductive disorders. CONCLUSION In conclusion, there is no significant difference between the level of awareness of PCOS among reproductive-aged female students from the Medical Technology degree program to the female students from the Pharmacy degree program